Mast Cells as Regulators of T Cell Responses - Bulfone-Paus, Silvia; Bahri, Rajia (Frontiers in Immunology, 2015)
Mast cells (MCs) are recognized to participate in the regulation of innate and adaptive immune responses. Owing to their strategic location at the host–environment interface, they control tissue homeostasis and are key cells for starting early host defense against intruders. Upon degranulation induced, e.g., by immunoglobulin E (IgE) and allergen-mediated engagement of the high-affinity IgE receptor, complement or certain neuropeptide receptors, MCs release a wide variety of preformed and newly synthesized products including proteases, lipid mediators, and many cytokines, chemokines, and growth factors. Interestingly, increasing evidence suggests a regulatory role for MCs in inflammatory diseases via the regulation of T cell activities. Furthermore, rather than only serving as effector cells, MCs are now recognized to induce T cell activation, recruitment, proliferation, and cytokine secretion in an antigen-dependent manner and to impact on regulatory T cells. This review synthesizes recent developments in MC–T cell interactions, discusses their biological and clinical relevance, and explores recent controversies in this field of MC research.